Rancang Bangun Sistem Informasi Akademik Berbasis Website Menggunakan Metode Design Science Research Methodology (Studi Kasus: SMK Veteran 1 Tulungagung) - Sanggara, Arganata; Cahyono, Taufik Agung; Prasetya, Agung (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Academic data management at SMK Veteran 1 Tulungagung still faces obstacles in the form of manual administrative processes, unintegrated data, reporting delays, and limited access to real-time information. These conditions indicate the need to develop an academic information system capable of supporting more effective and concise data management. This study aims to develop a website-based Academic Information System (SIAKAD) to improve the efficiency of academic administration management in the school environment. The research method uses the Design Science Research Methodology (DSRM) approach through the stages of problem identification, design, development, implementation, and system evaluation. The results of functional testing using Black Box Testing show that all features run as needed with a 100% success rate. Usability evaluation using the System Usability Scale (SUS) obtained an average score of 75.23 which is included in the acceptable category with a good level of user acceptance. In addition, performance testing shows that the system has a fast page loading time with a Largest Contentful Paint (LCP) value of under 1 second. The results of the study indicate that the developed SIAKAD is able to integrate academic data management in a single opening platform, simplifying information access, and supporting increased effectiveness of educational administration in vocational schools